Simple coordination and cognitive stimulation activities for cognitive function assessments using functional near-infrared spectroscopy - Norsham Juliana,; Izuddin Fahmy Abu,; Mohamad Haiqal Nizar Mohamad,; Muhammad Fattah Fazel,; Nurul Athirah Rani,; Nur Zafirah Farhana Zafreen,; Nor Azila Noh,; Zalhan Md Yusuf,; Muhammad Hafiz Laili,; Srijit Dass, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Functional near-infrared spectroscopy (fNIRS) is a non-invasive and high-density imaging device used for the evaluation of cognitive functions by measuring the oxygenated haemoglobin (HbO) and deoxygenated haemoglobin (HHb) levels in the prefrontal cortex. The present study determined the utilisation of fNIRS in detecting cerebral haemoglobin oxygenation level during coordination and simple cognitive stimulation activities in healthy young volunteers. Thirty subjects comprising equally of both genders were recruited. Subjects were tasked with coordination tests (plate tapping and block transfer tests) and cognitive stimulation activities (ruler drop test and MRAVLT) while the fNIRS system was attached to their prefrontal cortex area. The HbO and HHb levels were recorded and analysed using Repeated Measures ANOVA. The HbO levels during coordination tests differ significantly from resting state (p<0.05) in all but channel 2. All coordination tests elevated HbO levels compared to resting state except during block transfer test in channel 1. No significant difference was observed in HHb levels between coordination tests and resting state in all channels (p>0.05), except channel 3. All cognitive stimulation activities increased HbO levels compared to resting state; this change was significant in channels 3 and 4 (p<0.05). In contrast, HHb levels during all cognitive tests were lower compared to the resting state and was found to be significant in channels 2 and 3 (p<0.05). These findings suggested that coordination and cognitive stimulation activities activate prefrontal cortex in healthy young adults and could be potentially utilised as a valid screening tool for cognitive function assessments via fNIRS.